Quality and Fruit Production Improvement Using The Cultivation Technology System "ToPAS" In 12 Varieties of Hybrid Watermelons - Anung Wahyudi; Ratna Dewi (Jurnal Penelitian Pertanian Terapan, 2017)
The quality and production of watermelon in Indonesia is low relatively. We introduced "ToPAS" (toping, pruning, arranging and selection), the innovation of cultivation technology in an effort to improve the quality and production of watermelon. Our study was conducted in State Polytechnic of Lampung yield trials from May~August 2014, and used 12 varieties of hybrid watermelons with randomized block design two factors. The results of variance analyses in "ToPAS" system showed that productivity of watermelon fruit (oval and round type) are higher compared with conventional cultivation systems. We suggested using "ToPAS" system in watermelon cultivation to improve the cultivation technology, increasing quality and production of watermelon fruit. â€œToPASâ€ also suggested for watermelon breeding program.Key word : cultivation, production, ToPAS, watermelon